2021
DOI: 10.1002/aur.2635
|View full text |Cite
|
Sign up to set email alerts
|

The autistic brain can process local but not global emotion regularities in facial and musical sequences

Abstract: Whether autism spectrum disorder (ASD) is associated with a global processing deficit remains controversial. Global integration requires extraction of regularity across various timescales, yet little is known about how individuals with ASD process regularity at local (short timescale) versus global (long timescale) levels. To this end, we used event‐related potentials to investigate whether individuals with ASD would show different neural responses to local (within trial) versus global (across trials) emotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…Similarly, in depressed patients show reduced P300 to local oddballs before antidepressant treatment compared to healthy control group. Interestingly, after medication treatment, the depressed group recovered the P300 response to similar levels as in healthy controls 104 . These results suggest that as patients improve clinically, they may be retuning their predictive capabilities.…”
Section: Clinical Populationsmentioning
confidence: 64%
See 1 more Smart Citation
“…Similarly, in depressed patients show reduced P300 to local oddballs before antidepressant treatment compared to healthy control group. Interestingly, after medication treatment, the depressed group recovered the P300 response to similar levels as in healthy controls 104 . These results suggest that as patients improve clinically, they may be retuning their predictive capabilities.…”
Section: Clinical Populationsmentioning
confidence: 64%
“…In addition, ScZ exhibits a reduction of MMN responses to local oddballs [101][102][103] . An ASD study showed no responses to global oddball processing; however, there was enhanced local oddball visual processing 104 .…”
Section: Clinical Populationsmentioning
confidence: 95%
“…These findings suggest that there may be abnormalities in global prediction within the ASD population. In addition, individuals with ASD demonstrated MMN in response to violations of local emotion regularity for both faces and music, but their responses to global emotion regularity violations were absent [49]. These results, derived from a group level analysis, suggest a potential deficiency in global prediction within ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have argued that these people actually confuse their emotional experience with the emotions expressed by the music [6]. Emotions are closely related to human needs, and because music itself cannot satisfy the goals or desires of reallife listeners, it cannot evoke "real" tangible feelings such as "sadness" [7][8][9].…”
Section: Introductionmentioning
confidence: 99%